Gender bias and the fatherless phenomenon: Qur’an-based holistic guidance for children’s behavioral development - Fatmah, Nor (Jurnal Anifa: Studi Gender dan Anak, 2025)
Every individual aspires to a harmonious and nurturing family environment supported by both parents. However, in contemporary society, persistent gender stereotypes often position men primarily as breadwinners, while domestic and caregiving responsibilities are assigned almost exclusively to women. This imbalance has contributed to the growing phenomenon of fatherlessness, defined as a condition in which children experience the absence of a father figure either physically, psychologically, or both. Such conditions have increasingly affected children’s behavioral development. This study aims to examine the impact of fatherlessness on children’s behavioral development and to explore Qur’an-based guidance for addressing this phenomenon. Employing a literature-based research design with a psychological approach, data were collected through thematic analysis of relevant scholarly works and Qur’anic texts, and analyzed using a descriptive-analytical method. The findings indicate that fatherless conditions are associated with a heightened risk of behavioral problems in children, including tendencies toward deviant behavior and violations of social and legal norms. The Qur’an offers preventive and restorative guidance by emphasizing the importance of emotional bonding between parents and children, positive communication, and nurturing parental involvement. One recommended approach involves warm, affectionate, and enjoyable forms of communication—such as addressing children with positive and endearing expressions—which can foster strong emotional attachment and support healthy psychological development. This study contributes to the fields of child developmental psychology and Islamic family studies by providing a Qur’an-based framework for understanding and addressing fatherlessness within modern family life. It highlights the relevance of integrating religious ethical principles with psychological perspectives to promote balanced parental involvement and positive child development.